Analisis Resiko Kejadian Akut Rekuren Demam Tifoid dan Hubungannya dengan Kadar Protein Nucleotide Binding Oligomerization Domain 2 (NOD2) - Sri Wahyuni; Mochammad Hatta; Firdaus Hamid; Rosdiana Natzir; Ahyar Ahmad; Burhanuddin Bahar; Ade Rifka Junita; Ressy Dwiyanti; Nur Indah Purnamasari; Muhammad Reza Primaguna; Muhammad Sabir (Jurnal Ilmu Alam dan Lingkungan, 2021)
Typhoid fever is an infectious disease caused by Salmonella typhi bacteria and is endemic. The NOD2 gene is one of the host susceptibility genes in people with typhoid fever. NOD2 acts as an intracellular receptor that binds to the muramyl dipeptide ligand derived from bacterial peptidoglycan. The purpose of this study was to determine the levels of NOD2 protein in Acute Recurrent of Typhoid Fever (ARTF), typhoid fever (TF) patients, and healthy people (HP). Enzyme-linked Immunosorbent Assay (ELISA) was used to analyze NOD2 levels. The data analysis used was the student t-test. A significant difference of NOD2 level was found between the ARTF and TF group compared HP group (p